THE IMPACT OF SMOKING ON MALE REPRODUCTIVE HORMONE LEVELS AND INFERTILITY IN JEDDAH - S. Abosaber, Nourah (LIFE: International Journal of Health and Life-Sciences, 2024)
Tobacco use is overgrowing in all Arab countries and is one of the greatest threats to current and future global health. The negative effect of tobacco use on sperm quality has been examined in numerous studies. In Saudi Arabia, especially in Jeddah, this systematic research aims to investigate the impact of smoking on the hormonal profile in 75 men between the ages of 19 and 60 years who were randomly selected between smokers, infertile and nonsmokers from patients visiting King Abdulaziz University Medical Services Center and Health plus fertility & woman’s health center in Jeddah, SA. Chemiluminescent immunoassay technology was used to analyze data. Overall findings demonstrated no significant influence of smoking on testosterone, FSH, LH and prolactin levels in Saudi men.